# Calculator search results

Formula
Solve the equation
Graph
$y = 2 x + 3$
$y = 5 x + 9$
$x$-intercept
$\left ( - \dfrac { 3 } { 2 } , 0 \right )$
$y$-intercept
$\left ( 0 , 3 \right )$
$x$-intercept
$\left ( - \dfrac { 9 } { 5 } , 0 \right )$
$y$-intercept
$\left ( 0 , 9 \right )$
$2x+3 = 5x+9$
$x = - 2$
 Solve a solution to $x$
$2 x + 3 = \color{#FF6800}{ 5 } \color{#FF6800}{ x } + 9$
 Move the variable to the left-hand side and change the symbol 
$2 x + 3 \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } = 9$
$2 x \color{#FF6800}{ + } \color{#FF6800}{ 3 } - 5 x = 9$
 Move the constant to the right side and change the sign 
$2 x - 5 x = 9 \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } = 9 - 3$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 9 - 3$
$- 3 x = \color{#FF6800}{ 9 } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
 Subtract $3$ from $9$
$- 3 x = \color{#FF6800}{ 6 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
 Change the sign of both sides of the equation 
$3 x = - 6$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 그래프 보기 
Graph
Solution search results